IMPLEMENTASI SISTEM TOTAL PRODUCTIVE MAINTENANCE DI MESIN CUTTING LASER TIPE CMA1405-FET-N - iskandar, cecep andiyana abdul latif (Universitas Majalengka, 2024)
Every equipment and machine in every company. Requires a system to maintain the quality and quantity of the production process. With this, the system used in every company to realize the company's vision and mission, the system in question is the Total Productive Maintenance system. Every machine requires maintenance to maintain the quality of the machine, to avoid damage to the machine. Damage to the machine occurs due to obstacles in the production process, material fatigue, wear, component failure, design errors, or improper use. Machine damage is very detrimental to production results, including: Production downtime, machine damage continues, machine life is reduced, production quality is poor, and production costs increase. With the Total Productive Maintenance system, you can avoid losses from machine breakdown. PT. Shoetown Ligung Indonesia implements a TPM system in one of its management to optimize the production process